2021
DOI: 10.3390/cells11010033
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Lymphatic Metastasis in Infection and Immunity

Abstract: Lymphatic vessels permeate tissues around the body, returning fluid from interstitial spaces back to the blood after passage through the lymph nodes, which are important sites for adaptive responses to all types of pathogens. Involvement of the lymphatics in the pathogenesis of bacterial infections is not well studied. Despite offering an obvious conduit for pathogen spread, the lymphatic system has long been regarded to bar the onward progression of most bacteria. There is little direct data on live virulent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 206 publications
(356 reference statements)
0
4
0
Order By: Relevance
“…In five young horses, the perirectal abscesses were suspected to be due to anorectal lymphadenopathy, as mainly lymphocytes were found in the fine‐needle aspirate of three of these horses (Magee et al, 1997). Following haematogenous or lymphatic spread of pyogenic bacteria into a lymph node, a suppurative lymphadenitis can result in lymph node abscess formation (Fraser, 2009; Siggins & Sriskandan, 2022). Whether the young horses presented here also suffered from an abscessed lymph node remains unclear, as neither fine‐needle aspirates nor biopsies of the altered tissue were taken.…”
Section: Discussionmentioning
confidence: 99%
“…In five young horses, the perirectal abscesses were suspected to be due to anorectal lymphadenopathy, as mainly lymphocytes were found in the fine‐needle aspirate of three of these horses (Magee et al, 1997). Following haematogenous or lymphatic spread of pyogenic bacteria into a lymph node, a suppurative lymphadenitis can result in lymph node abscess formation (Fraser, 2009; Siggins & Sriskandan, 2022). Whether the young horses presented here also suffered from an abscessed lymph node remains unclear, as neither fine‐needle aspirates nor biopsies of the altered tissue were taken.…”
Section: Discussionmentioning
confidence: 99%
“…It is already known that a high percentage of the immune system is located in the gut, thus there are higher possibilities for such colonies to be transformed. Importantly, it has been demonstrated that the extracellular bacterial lymphatic metastasis of the virulent strains of certain streptococci drives systemic infection, and there have also been illustrated multifarious routes and mechanisms by which an increasing variety of bacteria are acknowledged to transit through the lymphatic system, including those that do not necessarily require internalization by host cells [ 1224 ]. Therefore, one can already have organ inflammation and possible subsequent other system inflammation (i.e., nervous system inflammation) due to systemic inflammation, and realize it after being symptomatic for any system (i.e., muscle symptoms and underlying systemic acidosis) by random or due to genetic factors.…”
Section: The Expert’s Opinion: a Critical Appraisal Of The Current Li...mentioning
confidence: 99%
“…In the context of inflammatory processes, the lymphatic vascular network appears to be expanded due to lymphatic hyperplasia and abnormal lymphangiogenesis ( 6 ), as shown in both mouse models and patient samples of inflammatory diseases, such as arthritis ( 7 ), atopic dermatitis ( 8 ), psoriasis ( 9 ), and inflammatory bowel disease ( 10 ). Distorted function of LVs has been also associated with cardiometabolic diseases ( 11 ), infection diseases ( 12 ), and more recently, neurodegenerative pathologies ( 13 ).…”
Section: Introductionmentioning
confidence: 99%